Potensi Nilai Arsitektur Neo-Vernakuler dalam Rumah Adat Bale Tani di Lombok - Muhammad Yumna Hilmy Labib (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2023)
Sade Village is a unique village which becomes the gate of the nature of the Sasak tribe of Lombok. One of the cultural products of the Sasak tribe is the Bale Tani and Bale Lumbung traditional houses. However, the popularity of Bale Tani is far less popular than Bale Lumbung. This study aims to demonstrate the potential of Bale Tani as a neo-vernacular architectural design that is sustainable against the times. This study describes the comparison between Bale Tani and Bale Lumbung in terms of popularity, utility, and aesthetics. This study also visualizes Bale Tani as a reference for the prototype design of a modern house with the theme Green Building in Tropical. The primary source of this research was obtained from a public survey which was conducted online while the secondary source was obtained from intensive studies of various books and journals, both national and international. The results of the study show that Bale Tani has the potential to be developed into a neo-vernacular building that has aesthetics, utility, and sustainability that is superior to the conventional Bale Tani. Researchers hope that, as a nation rich in culture, we must preserve our culture so that it will not be consumed by the times. This can be done by uniting determination and cooperation between the community and the government. Bale Tani neo-vernacular can be one proof of the preservation of our culture.